Comparison of the Relative Fibrinogenolytic, Fibrinolytic and Thrombolytic Properties of Tissue Plasminogen Activator and Urokinase in Vitro - Matsuo, O; Rijken, D C; Collen, D (Thrombosis and Haemostasis, 1981)
The relative fibrinogenolytic, fibrinolytic and thrombolytic properties of human tissue plasminogen activator and human urokinase were compared in purified systems, in whole human plasma and in a system composed of a radioactive human blood clot (125I-fibrinogen) hanging in circulating human plasma. The human tissue plasminogen activator was highly purified from the culture fluid of a human melanoma cell line.In purified systems composed of fibrinogen or fibrin, plasminogen and α2-antiplasmin as well as in whole plasma, tissue plasminogen activator digested fibrin without degrading fibrinogen significantly. Urokinase did not have this specific fibrinolytic effect.In the circulating plasma system, the degree of fibrinolysis was proportional to the amount of activator added, tissue plasminogen activator being about 10 times more efficient than urokinase. In addition, tissue plasminogen activator appeared to cause negligible fibrinogen degradation. Tissue plasminogen activator still induced significant thrombolysis at a concentration of 10 IU per ml whereas no effect of urokinase was observed at 20 IU per ml. Infusion of 100 IU (1 (μg) of tissue plasminogen activator per ml resulted in moderate activation of the fibrinolytic system as judged from a decrease of plasminogen and α2-antiplasmin to 40-50 percent. Nevertheless, extensive fibrinolysis (50 to 80 percent of radioactivity released after 12 hrs) and only very limited fibrinogenolysis were observed. An equivalent amount of urokinase (100 IU per ml) only induced approximately 15 percent lysis in 12 hrs. At higher concentrations of urokinase (260 IU per ml or more) extensive activation of the fibrinolytic system was obtained as evidenced by a depletion of plasminogen, α2-antiplasmin and fibrinogen. This was associated with extensive fibrinolysis (approximately 60 percent after 12 hrs). It is concluded that human tissue plasminogen activator is a more specific and effective fibrinolytic-thrombolytic agent than human urokinase.
Keywords: Tissue plasminogen activator; Urokinase; Fibrinogenolysis; Fibrinolysis; Thrombolysis